Smart Data: A New Perspective of Tackling the Big Data Phenomena Leveraging a Fog Computing System - Farhoud Hosseinpour; Juha Plosila; Hannu Tenhunen (Advanced Institute of Convergence Information Technology, 2022)
The management of Big Data is a very important issue in emerging IoT technologies. Conventional methods are not sufficient to deal with the ever-increasing amount of raw data originating from the sensors. In this paper we approach this problem from the data structure perspective. We design and develop a concept that we call “Smart Data”. Smart Data is an active and intelligent data structure using a fog computing system that facilitates the management of Big Data in IoT based applications. Such a data cell is initially very simple and lightweight, but it evolves (grows) when traveling through the hierarchical fog computing system towards the cloud, merging with other cells or vice-versa, if the data moves from the cloud towards the actuators. Using Smart Data, we aim to facilitate the preprocessing of data to reduce the load from cloud computing and improve the quality of service and energy efficiency in IoT applications. Our main targets for pre-processing of Big Data using Smart Data and fog computing platform include data filtering, aggregation, compression, and encryption. Moreover, our design goal is to reduce volume, velocity and increase value and veracity of Big Data considering other parameters such as energy efficiency, throughput, scalability and quality of service.